Selective degradation of hemicellulose and lignin for improving enzymolysis efficiency via pretreatment using deep eutectic solvents. (May 2023) - Huo, Dan; Sun, Yuekai; Yang, Qiulin; Zhang, Fengshan; Fang, Guigan; Zhu, Hongxiang; Liu, Ying
Graphical abstract: Highlights: Deep eutectic solvents pretreatment was sustainability and low carbon. Carboxyl, Cl − and N + in DESs had stronger hydrogen bond destruction ability. DESs-AlCl3 had excellent efficiency for its polyhedral coordination species. 90% of non-cellulosic constituent removal improved the enzymolysis efficiency. Abstract: Deep eutectic solvents (DESs) with different acidity and alkalinity were applied for biomass pretreatment, and the conditions were optimized by response surface methodology. The results showed that lactic acid/betaine hydrochloride had the optimal pretreatment efficiency, where the removal rates of hemicellulose and lignin came up to 89% and 73%, and the enzymolysis efficiency was as high as 92%. Furthermore, eight types of chloride salts with different valence states were introduced into the DESs as the third component. The chloride salts could improve the pretreatment efficiency and positively correlated with the metal valence state. Specifically, AlCl3 was significantly superior in improving the pretreatment efficiency, where the enzymolysis efficiency reached 96% due to the destruction of crystalline region and the esterification of partial cellulose. Therefore, it is proposed that adding highly valent metal salts to acidic DESs has higher pretreatment and enzymatic efficiency.